Intrauterine exposure to preeclampsia does not impair vascular health in children - Varley, Benjamin J.; Henry, Amanda; Roberts, Lynne; Davis, Gregory; Skilton, Michael R.; Craig, Maria E.; Gow, Megan L. (Frontiers in Public Health, 2022)
Background and Objectives: Preeclampsia is a serious multisystem blood pressure disorder during pregnancy that is associated with increased long-term risk of cardiovascular disease to the mother and offspring. We investigated the vascular health of children exposed to intrauterine preeclampsia. Materials and methods: This was a cross-sectional study of offspring in a prospective cohort of women with complications during pregnancy. Children aged between two and five years (median age 4.7 [2.8,5.1] years) exposed to intrauterine preeclampsia (n=26) or normotensive controls (n=34), were recruited between July 2020 and April 2021. Vascular health was assessed by measuring aortic intima-media thickness and pulse wave velocity. Univariate generalised linear regression models were used to explore associations between vascular measurements and explanatory variables. Results: Children exposed to preeclampsia had a lower body mass index at assessment (15.5 vs 16.2 kg/m2, p=.04), birth weight (2.90 vs 3.34 kg, p=.004), gestational age at birth (37.5 vs 39.4 weeks, p<.001) and higher frequency of preterm birth (27% vs 6%, p=.02). There were no differences in vascular health between children exposed to preeclampsia vs controls (mean aortic intima-media thickness 0.575 mm vs 0.563 mm, p=.51, pulse wave velocity 4.09 vs 4.18 m/s, p=0.54) and there were no significant associations in univariate analyses. Conclusions: There were no major adverse differences in vascular health which contrasts with existing studies. This suggests exposure to intrauterine preeclampsia may result in a less severe cardiovascular phenotype in young children. While reassuring, longitudinal studies are required to determine if and when exposure to intrauterine preeclampsia affects health in children.